Application of Accuracy and Precision Evaluations Based on the Current United States and Indonesian Pharmacopoeias: A Critical Review - Indrayanto, Gunawan (UI Scholars Hub, 2022)
New methods for the evaluation of accuracy and precision are mentioned in the latest edition of the United States Pharmacopoeia (USP), whereas other validation parameters, that is, selectivity, linearity, range, and robustness, remained relatively unchanged. In obtaining reliable data from any chemical/pharmaceutical analysis, the analytical procedure must be validated or verified in accordance with the latest edition of the pharmacopoeia. Some review articles on the general validation methods have been published by the author. This present review will focus on the implementation and discussion of the accuracy and precision evaluation based on the current USP and Indonesian pharmacopoeia. Some examples of the calculation of several accuracy and precision method of determinations are also discussed.